Pengaruh Manajemen Kas Terhadap Profitabilitas Pada PT. Indofood CBP Sukses Makmur Tbk - Nawal Putri Retisa; Muchriana Muchran; Muhammad Adil (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the effect of cash management on profitability at PT Indofood CBP Sukses Makmur Tbk. Cash management is an important factor in maintaining liquidity and stopping company operations, while profitability is the main indicator in assessing the company's financial performance. This study uses a quantitative approach with secondary data in the form of the company's annual financial report for the period 2020–2023. The independent variable in this study is cash management as measured by cash inflow and cash outflow, while the dependent variable is profitability as measured by Return on Assets (ROA) and Net Profit Margin (NPM). Data analysis was carried out using multiple linear regression tests and classical assumption tests with the help of SPSS software. The results of the study indicate that cash management has a negative effect on profitability, both in terms of ROA and NPM. This finding indicates that efficiency in cash management needs to be improved to support optimal company profit growth.